UY SICHQONI (MUS MUSCULUS)NING BIOEKOLOGIYASI VA ULAR BILAN KURASH USULLARI - Palvanova, G.J.; Qurbaniyazov, A.S. (SCIENCE and SOCIETY, 2025)
The article presents the materials of bioecological studies conducted in 2020-2024 on Musmusculus, a representative of the rodent order distributed in the Lower Amu Darya delta. The dynamics of the number of house mice (Mus musculus) are presented the distribution of the delta along the tugai and vegetation zones, and effective methods of combating them.